2023
DOI: 10.3390/ijms241914867
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Modifications Associated with Ovarian Cancer Cell Aggregation and Limited Culture Conditions

Joseph P. Grieco,
Stephanie L. E. Compton,
Grace N. Davis
et al.

Abstract: The aggregation of cancer cells provides a survival signal for disseminating cancer cells; however, the underlying molecular mechanisms have yet to be elucidated. Using qPCR gene arrays, this study investigated the changes in cancer-specific genes as well as genes regulating mitochondrial quality control, metabolism, and oxidative stress in response to aggregation and hypoxia in our progressive ovarian cancer models representing slow- and fast-developing ovarian cancer. Aggregation increased the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Further, the abdominal adipose tissues contain progenitor and stem cells in the stromal vascular fraction that can be recruited to ovarian metastases ( 31 ). We have recently shown that incorporation of the stromal cells supported the survival, adhesion and invasion of non-adherence ovarian cancer cell aggregates via reduced respiration and proliferation, as well as elevated expression of genes that increase senescence, telomere maintenance, and DNA repair ( 22 , 32 ). Whether the HFD changes the stem- and progenitor populations in the abdominal adipose tissues or affects their recruitment to disseminating ovarian metastases needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the abdominal adipose tissues contain progenitor and stem cells in the stromal vascular fraction that can be recruited to ovarian metastases ( 31 ). We have recently shown that incorporation of the stromal cells supported the survival, adhesion and invasion of non-adherence ovarian cancer cell aggregates via reduced respiration and proliferation, as well as elevated expression of genes that increase senescence, telomere maintenance, and DNA repair ( 22 , 32 ). Whether the HFD changes the stem- and progenitor populations in the abdominal adipose tissues or affects their recruitment to disseminating ovarian metastases needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of free fatty acids after ingestion of the HFD may contribute to the high levels of Ccl2 via activation of TLR4 ( 57 ). Ccl2 is also highly expressed in the MOSE-L TIC v cells but is even higher in stromal cells derived from obese adipose tissues, and increased in hypoxic conditions ( 32 ). Thus, the HFD-mediated increase in Ccl2 and its receptor promotes inflammation but also can enhance the autocrine CCL2-CCR2 axis that activates monocytes, macrophages, and NK cells, and promotes macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nutrient deprivation such as glutamine promotes the malignant biological behavior (e.g., stemness and chemoresistance) of ovarian cancer cells via DRP1-induced mitochondrial fragmentation with enhanced glycolysis [58]. Ovarian cancer cells can reprogram mitochondrial function and localization in response to intracellular energetic demands, the nutrient supply, and a hypoxic environment [34,59,60]. In addition, mitochondrial dynamics contribute to maintaining the regenerative competence of not only cancer cells but also normal cells through the activation of genes that control mitochondrial fusion and fission [39,61] (Figure 1, Stemness).…”
Section: Mitochondrial Fissionmentioning
confidence: 99%